Model Meningkatkan Niat Beli Produk Hijau: Sebuah Pendekatan Strategik - Jati Waskito; Banu Witono (Jurnal Ekonomi dan Bisnis, 2014)
This study aims to develop the results of previous research, as follows: 1) design and test a model of consumer perceptions (that has been mapped during year-1 of a comprehensive review of the eco-friendly products 2) analyze the factors (i.e. environmentally friendly corporate image, perceptions of environmentally friendly products, product labels, and government regulations) that influence purchasing decisions of eco-friendly products based on design and test result on the proposed model 3) identify the most important factors considered by the consumers through comprehensive model testing, so as to provide empirical evidence for the sake of implementing environmentally conscious marketing strategy.The results of the field survey managed to get 293 respondents who are willing to participate. The conclusions of the study are 1) the proposed research model in this study is able to represent a comprehensive picture of people’s perception on environmentally friendly products; 2) regulatory, corporate image, and product perceptions variables significantly shape the public perception of the eco-friendly products; 3) corporate image variable is the most important element in shaping public perceptions on environmentally friendly products.